Specific protocols of controlled ovarian stimulation for oocyte cryopreservation in breast cancer patients - Cavagna, Felipe; Pontes, A. [UNESP]; Cavagna, M.; Dzik, A.; Donadio, N. F.; Portela, R.; Nagai, M. T.; Gebrim, L. H. (MDPI, 2018)
Background Fertility preservation is an important concern in breast cancer patients. In the present investigation, we set out to create a specific protocol of controlled ovarian stimulation (cos) for oocyte cryopreservation in breast cancer patients. Methods From November 2014 to December 2016, 109 patients were studied. The patients were assigned to a specific random-start ovarian stimulation protocol for oocyte cryopreservation. The endpoints were the numbers of oocytes retrieved and of mature oocytes cryopreserved, the total number of days of ovarian stimulation, the total dose of gonadotropin administered, and the estradiol level on the day of the trigger. Results Mean age in this cohort was 31.27 ± 4.23 years. The average duration of cos was 10.0 ± 1.39 days. The mean number of oocytes collected was 11.62 ± 7.96 and the mean number of vitrified oocytes was 9.60 ± 6.87. The mean estradiol concentration on triggering day was 706.30 ± 450.48 pg/mL, and the mean dose of gonadotropins administered was 2610.00 ± 716.51 IU. When comparing outcomes by phase of the cycle in which cos was commenced, we observed no significant differences in the numbers of oocytes collected and vitrified, the length of ovarian stimulation, and the estradiol level on trigger day. The total dose of follicle-stimulating hormone and human menopausal gonadotropin administered was statistically greater in the group starting cos in the luteal phase than in the group starting in the late follicular phase. Conclusions Our results suggest that using a specific protocol with random-start ovarian stimulation for oocyte cryopreservation in breast cancer patients is effective and could be offered to young women undergoing oncologic treatment.
Keywords: Breast cancer; Fertility preservation; Oocyte cryopreservation; Ovarian stimulation